2012
DOI: 10.4236/aces.2012.23039
|View full text |Cite
|
Sign up to set email alerts
|

Application of Polymeric Membrane in CO<sub>2</sub> Capture from Post Combustion

Abstract: CO 2 capture from post combustion does not need significant alteration of the current power generation facilities and is therefore of more interests to the research and industrial circles. Polymeric membrane separations, which are based mainly on physical phenomena, are easy for operation and to scale up. The details and future research trends are covered in this most updated review, which serve as an excellent technique reference for the research circle and technology evaluation for the related industrial cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Hence, the flow through the commercial membrane materials would be significantly low in the absence of a compressing assembly for the air supply in gas separation membrane operations. These membranes also have a permeability and selectivity trade-off, which limits their general applicability, especially when high performance is required. The ultrathin poly­vinyl­amine (PVAm) membrane based on polysulfone was assessed, and preliminary gas separation results (selectivity ∼ 200, permeance approximately 1 m 3 STP /bar·h·m 2 ) indicate potential in the field of CO 2 capture from flue gas . These recently developed novel assisted membranes can achieve 90% purity and 90% CO 2 recovery from flue gas mixtures even at a CO 2 concentration of 10%, as shown in Figure …”
Section: Methods Of Dacmentioning
confidence: 99%
“…Hence, the flow through the commercial membrane materials would be significantly low in the absence of a compressing assembly for the air supply in gas separation membrane operations. These membranes also have a permeability and selectivity trade-off, which limits their general applicability, especially when high performance is required. The ultrathin poly­vinyl­amine (PVAm) membrane based on polysulfone was assessed, and preliminary gas separation results (selectivity ∼ 200, permeance approximately 1 m 3 STP /bar·h·m 2 ) indicate potential in the field of CO 2 capture from flue gas . These recently developed novel assisted membranes can achieve 90% purity and 90% CO 2 recovery from flue gas mixtures even at a CO 2 concentration of 10%, as shown in Figure …”
Section: Methods Of Dacmentioning
confidence: 99%
“…Also it was shown that at gap spacing of 3 to 5 mm the removal efficiency increased to a maximum. Wang and Han reviewed CO 2 capture with polymeric Membrane [16]. According to them, hollow fiber membrane is highly gas permeable.…”
Section: An Insight Into Removal and Recovery Of So 2 And Co 2 In Petmentioning
confidence: 99%
“…Although much work has been performed on material modification to fine-tune gas transport properties, the relationship of permselectivity to the polymer microstructure is still under investigation. Most common applications include hydrogen recovery, hydrogen separation for ammonia recovery, air separation for nitrogen production or oxygen enrichment, carbon dioxide removal from industrial processes, and removal of impurities in natural gas supplies. , The separation of N 2 and CO 2 from CH 4 is important in natural gas processing because N 2 and CO 2 are incombustible. However, N 2 /CH 4 separation is technically challenging because of the similar molecular size of N 2 (∼0.36 nm) and CH 4 (∼0.38 nm) .…”
Section: Introductionmentioning
confidence: 99%